Meningkatkan Hasil Belajar Operasi Hitung Bilangan Pecahan dengan Kartu Bilangan Siswa Kelas VI SD Negeri Krueng Baung - Nurdiana Nurdiana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Improving mathematics learning outcomes is one of the important goals that students are expected to achieve in learning mathematics, but in reality the majority of students still have difficulty understanding the fractional number calculation operations they are studying. This research aims to improve the learning outcomes of fractional number counting operations using number cards. The type of research is classroom action research with all class VI students at SDN Krueng Baung for the 2020/2021 academic year as research subjects. This research is said to be successful if it meets the indicators of success, namely: (1) the average score of learning outcomes for students' fractional counting operations increases and meets the minimum completeness criteria, namely 75; and (2) the percentage of students who complete increases and reaches ≥ 75% of the total number of students. The research results showed that: (1) in Cycle I the average assignment score was 65.55 and the percentage of students who completed it was 27.28%, (2) while in Cycle II the average assignment score was 85.27 and the percentage of students who completed it was 83.33%, and (3) there was an increase in the average assignment score from Cycle I to Cycle II by 19.72 and there was an increase in the test score from Cycle I to Cycle II by 20.55. The conclusion obtained is that the application of the number card method can improve the learning outcomes of fractional number calculation operations for Class VI students at SDN Krueng Baung for the 2020/2021 academic year. For teachers who teach Mathematics subjects in elementary schools, it is necessary to use learning media that is appropriate to the material being discussed, so that the learning atmosphere for Mathematics subjects is not in a tense atmosphere but instead in a pleasant atmosphere.